Cerdas Digital Sehat Mental,Membangun Generasi Muda yang Bijak dan Produktif di Era Digital pada Karang Taruna Diponegoro: Digitally Smart, Mentally Healthy, Building a Wise and Productive Young Generation in the Digital Era at Karang Taruna Diponegoro - Rimawati, Elistya; Vinahapsari, Cinthia Annisa; Saptomo, Wawan Laksito Yuly; Azizah, Umi Fajar; Adji, Aulia Gustin San; Marsudi, Lexsa Sifa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This Community Engagement Program aims to address three main problems faced by the Diponegoro Youth Organization (Karang Taruna): a lack of digital literacy and data security, low awareness of mental health, and the suboptimal use of technology for productivity. To tackle these issues, the implementing team applied a participatory approach through a detailed series of activities, covering: Initiation and Collaboration, Training Program Preparation, Training Implementation (in the form of workshops), Intensive Mentoring, and Monitoring and Evaluation The themes for the intensive workshops and mentoring consisted of three main issues: Mental Resilience in the Digital Era, Affiliate Digital Marketing, and Personal Data Security. This program has produced several key outputs, both tangible and social. Three guidebooks (Emotional Intelligence in the FOMO Era; Affiliate Marketing: Turn Social Media into a Money Machine; and Early Detection, Self-Protection), instructional videos, and an X-Banner for the "Digital Smart, Mental Health" campaign were created and delivered to the Diponegoro Youth Organization. The program was featured in national mass media, and its activity videos were uploaded to the official @TSUOFFICIAL YouTube channel. Several training participants have begun practicing digital marketing and have successfully earned income as affiliates, though the amounts remain modest. This demonstrates a positive start in utilizing technology for economic purposes. As part of the program's sustainability, the "Gatak Village Digital Youth Group" was formed as a forum for members to share knowledge and support one another. This established Digital Youth Group ensures that the positive impact continues to expand within the community.